Composite internal curing material for ultra-high performance concrete and preparation method of composite internal curing material

By coating natural aggregates with an MPC/CNT composite coating in UHPC, the self-shrinkage problem is solved, the mechanical properties and durability of the material are improved, and intelligent functions are added, achieving efficient internal curing of UHPC.

CN121449360APending Publication Date: 2026-02-03中国建筑工程(澳门)有限公司 +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511472779.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-15
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

Existing technologies have limitations in suppressing the autogenous shrinkage of ultra-high performance concrete (UHPC). Traditional internal curing materials may reduce the strength and durability of the material, and organic shrinkage reducing agents have problems such as poor compatibility and easy aging.

Method used

An MPC/CNT composite coating is applied to the surface of natural aggregates. By optimizing the pore structure to store and slowly release moisture, a continuous three-dimensional conductive network is constructed, enhancing the interface transition zone and forming a highly efficient internal curing material.

Benefits of technology

Significantly reduces the risk of early cracking in UHPC, improves the mechanical properties and durability of the material, and endows it with stress and strain self-sensing and electromagnetic shielding functions, providing a key material foundation for intelligent civil engineering structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121449360A_ABST
    Figure CN121449360A_ABST
Patent Text Reader

Abstract

The invention relates to a composite internal curing material for ultra-high performance concrete and a preparation method of the composite internal curing material. 100 to 160 parts of natural aggregate; 5 to 12 parts of magnesium oxide, 1.5 to 3.5 parts of ammonium dihydrogen phosphate, 1.5 to 5 parts of deionized water and 0.5 to 1.2 parts of carbon nanotube; wherein the magnesium oxide, the ammonium dihydrogen phosphate, the deionized water and the carbon nanotubes are treated to form an MPC / CNT composite coating, and the surface of the natural aggregate is coated with the MPC / CNT composite coating. By means of the MPC / CNT composite coating, water is efficiently stored and slowly released through an internal optimized multi-stage pore structure, and chemical shrinkage in the UHPC hydration process is accurately compensated. Meanwhile, the coating enhances the hydration degree of a matrix and strengthens an aggregate-slurry interface transition area, so that the self-constriction micro-strain is remarkably reduced, and the early cracking risk of the material is fundamentally reduced.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of building materials, in particular to a composite internal curing material for ultra-high performance concrete and a preparation method thereof. BACKGROUND

[0002] Ultra-high performance concrete (UHPC) has been widely used in modern construction fields such as high-rise buildings, long-span bridges and national defense engineering due to its excellent mechanical strength, superior durability and good toughness. However, in order to achieve ultra-high performance, UHPC usually adopts a very low water-binder ratio and a large amount of cement-based binder, which leads to a rapid and intense hydration reaction in the early stage of hardening. In this process, the water in the internal capillary pores is rapidly consumed, forming a significant capillary underpressure, which triggers a serious autogenous shrinkage phenomenon. This internal volume reduction easily leads to early cracking of the material, which not only reduces the load-carrying capacity and density of the structure, but also provides a channel for the intrusion of harmful media, severely restricting its long-term durability and service life.

[0003] To suppress the autogenous shrinkage of UHPC, traditional methods include introducing saturated lightweight aggregate, superabsorbent polymer (SAP) and other internal curing materials, or adding organic shrinkage-reducing agents (SRA). However, these methods have obvious limitations: saturated lightweight aggregate has low strength and may become a weak link in the system; macroscopic pores left by SAP after water release can damage the final strength and durability of the material; and organic shrinkage-reducing agents have poor compatibility with the cement matrix, are prone to aging, have long-term performance degradation, and may delay hydration. Therefore, developing a new type of internal curing material that can efficiently suppress autogenous shrinkage without sacrificing other excellent properties of UHPC, or even endowing it with new functions, has become a key technical problem that needs to be solved in this field. SUMMARY

[0004] The present application aims to provide a composite internal curing material for ultra-high performance concrete and a preparation method thereof, to solve the problems raised in the background art.

[0005] To achieve the above-mentioned purpose, the technical solutions of the present application are as follows.

[0006] A composite internal curing material for ultra-high performance concrete and a preparation method thereof, comprising the following components by mass:

[0007] 100-160 parts of natural aggregate;

[0008] 5-12 parts of magnesium oxide, 1.5-3.5 parts of ammonium dihydrogen phosphate, 1.5-5 parts of deionized water, and 0.5-1.2 parts of carbon nanotubes;

[0009] The magnesium oxide, the ammonium dihydrogen phosphate, the deionized water and the carbon nanotube are treated to form a MPC / CNT composite coating, and the MPC / CNT composite coating is coated on the surface of the natural aggregate.

[0010] Further, the natural aggregate is quartz sand, and the particle size of the quartz sand ranges from 0.707 mm to 1.19 mm.

[0011] Further, the thickness of the MPC / CNT composite coating ranges from 20 microns to 100 microns, and the MPC / CNT composite coating has a pore structure with a pore size ranging from 10 nanometers to 10 microns.

[0012] Further, the carbon nanotube is a multi-walled carbon nanotube, and the length of the multi-walled carbon nanotube ranges from 1 micrometer to 20 micrometers, and the diameter of the multi-walled carbon nanotube ranges from 5 nanometers to 20 nanometers.

[0013] The application further provides a preparation method of the composite internal curing material for the ultra-high performance concrete.

[0014] 1) The magnesium oxide and the ammonium dihydrogen phosphate are mixed at a mass ratio of 3-4.5:1 to prepare a dry powder of MPC. The carbon nanotube is added to the prepared MPC powder at 10% of the mass of the magnesium oxide, and the MPC composite powder modified by the carbon nanotube is obtained after ball milling. Finally, the deionized water is added to the modified MPC composite powder, and the MPC / CNT composite slurry is obtained after continuous stirring until the system is uniform.

[0015] 2) The natural aggregate is placed in a fluidized bed device to keep the natural aggregate in a fluidized state. The MPC / CNT composite slurry is applied to the natural aggregate in the fluidized state to complete the coating operation.

[0016] 3) The coated natural aggregate is cured until the coating is completely solidified, and the composite internal curing material for the ultra-high performance concrete is obtained.

[0017] Further, in step 1, the rotation speed of the ball mill ranges from 600 r / min to 1200 r / min, and the ball milling time ranges from 0.5 h to 1 h.

[0018] Further, in step 3, the curing is performed in a constant-temperature and constant-humidity curing mode, the curing conditions are a temperature of 20-25℃ and a relative humidity of 80%-90%, and the curing time ranges from 24 h to 48 h.

[0019] Compared with the prior art, the application has the following beneficial effects.

[0020] 1.The present application stores and releases water efficiently through the internal optimized multi-level pore structure of the MPC / CNT composite coating, precisely compensating for the chemical shrinkage during the hydration process of UHPC. At the same time, the coating enhances the hydration degree of the matrix and strengthens the interfacial transition zone between the aggregate and the paste, thereby significantly reducing the self-shrinkage micro-strain and fundamentally reducing the risk of early cracking of the material.

[0021] 2.The present application builds a continuous three-dimensional conductive network in the cement matrix through uniformly dispersed carbon nanotubes, significantly reducing the volume resistivity of UHPC from nearly insulating to the order of 32kΩ·cm. This feature enables UHPC structures to have stress and strain self-awareness and electromagnetic shielding functions, providing a key material basis for the development of intelligent civil engineering structures.

[0022] 3.The inorganic MPC-based coating used in the present application has high chemical compatibility with the cement matrix, avoiding the defects of organic materials such as easy aging and easy degradation, and exhibiting higher chemical stability and environmental adaptability. At the same time, it effectively suppresses shrinkage while simultaneously improving the mechanical properties and durability of the material. BRIEF DESCRIPTION OF DRAWINGS

[0023] Figure 1 A flowchart of a preparation method of a composite internal curing material for ultra-high performance concrete is provided. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present application will be described clearly and completely below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.

[0025] Embodiment 1

[0026] This embodiment provides a composite internal curing material for ultra-high performance concrete and a preparation method thereof, which comprises the following components by mass: natural aggregate 100 parts, magnesium oxide 6 parts, ammonium dihydrogen phosphate 2.0 parts, deionized water 3.0 parts, and carbon nanotubes 0.6 parts.

[0027] Preparation process:

[0028] 1) Mix 6 parts of magnesium oxide and 2.0 parts of ammonium dihydrogen phosphate to prepare MPC dry powder;

[0029] 2) Add 0.6 parts of carbon nanotubes to the MPC powder and ball mill at a speed of 1000r / min for 1 hour;

[0030] 3) The composite powder after ball milling is mixed with 3.0 parts of deionized water, and continuously stirred until the system is uniform, to obtain MPC / CNT composite slurry;

[0031] 4) 100 parts of quartz sand aggregate are loaded into the hopper of the fluidized bed coating equipment, the equipment is started, hot air at 50°C is introduced, and the air volume is adjusted to make the aggregate in a uniform and stable fluidized state. The prepared MPC / CNT composite slurry is uniformly applied to the surface of the fluidized aggregate in the form of spray through the atomizing nozzle of the equipment, and the spraying process lasts for 15 minutes;

[0032] 5) The coated aggregate is taken out of the fluidized bed, laid flat in a tray, and ensured to be well ventilated. The tray is placed in a constant temperature and humidity curing box, and cured at a temperature of 25°C and a relative humidity of 85% for 36 hours, so that the MPC coating fully reacts and completely cures.

[0033] The final coating parameters are: thickness ~ 40 μm, porosity ~ 38%, and average pore size ~ 400 nm.

[0034] Example 2

[0035] This example gives a composite internal curing material for ultra-high performance concrete and a preparation method thereof, which comprises the following components by mass: natural aggregate 100 parts, magnesium oxide 8 parts, ammonium dihydrogen phosphate 2.8 parts, deionized water 2.0 parts, and carbon nanotubes 0.8 parts;

[0036] Preparation process:

[0037] 1) 8 parts of magnesium oxide and 2.8 parts of ammonium dihydrogen phosphate are mixed to prepare MPC dry powder;

[0038] 2) 0.8 parts of carbon nanotubes are added to the MPC powder, and ball milling is carried out at a speed of 1100 r / min for 0.8 hours;

[0039] 3) The composite powder after ball milling is mixed with 2.0 parts of deionized water, and continuously stirred until the system is uniform, to obtain MPC / CNT composite slurry;

[0040] 4) 100 parts of quartz sand aggregate are loaded into the hopper of the fluidized bed coating equipment, the equipment is started, hot air at 60°C is introduced, and the air volume is adjusted to make the aggregate in a uniform and stable fluidized state. The prepared MPC / CNT composite slurry is uniformly applied to the surface of the fluidized aggregate in the form of spray through the atomizing nozzle of the equipment, and the spraying process lasts for 18 minutes;

[0041] 5) The coated aggregate is taken out of the fluidized bed, laid flat in a tray, and ensured to be well ventilated. The tray is placed in a constant temperature and humidity curing box, and cured at a temperature of 25°C and a relative humidity of 80% for 48 hours, so that the MPC coating fully reacts and completely cures.

[0042] Final coating parameters: thickness ~ 65 pm, porosity ~ 35%, average pore size ~ 200 nm.

[0043] Example 3

[0044] The present example provides a composite internal curing material for ultra-high performance concrete and a preparation method thereof, comprising the following components by mass fraction: natural aggregate 100 parts, magnesium oxide 5 parts, ammonium dihydrogen phosphate 1.5 parts, deionized water 4 parts, and carbon nanotubes 0.5 parts.

[0045] Preparation process:

[0046] 1) Mix 5 parts of magnesium oxide and 1.5 parts of ammonium dihydrogen phosphate to prepare MPC dry powder;

[0047] 2) Add 0.5 parts of carbon nanotubes to the MPC powder, and ball mill at a speed of 900 r / min for 0.5 hours;

[0048] 3) Mix the ball-milled composite powder with 4.0 parts of deionized water, and continuously stir until the system is uniform to obtain MPC / CNT composite slurry;

[0049] 4) Put 100 parts of quartz sand aggregate into the hopper of the fluidized bed coating equipment, turn on the equipment, and introduce hot air at 40°C. Adjust the air volume to make the aggregate in a uniform and stable fluidized state. Through the atomizing nozzle of the equipment, uniformly apply the prepared MPC / CNT composite slurry in the form of spray to the surface of the fluidized aggregate. The spraying process lasts for 12 minutes;

[0050] 5) Take out the coated aggregate from the fluidized bed, lay it flat on a tray, make sure it is well ventilated, and place the tray in a constant temperature and humidity curing box. Curing at a temperature of 20°C and a relative humidity of 90% for 24 hours to make the MPC coating fully react and completely solidify.

[0051] Final coating parameters: thickness ~ 25 pm, porosity ~ 45%, average pore size ~ 1.2 pm.

[0052] Example 4

[0053] The present example provides a composite internal curing material for ultra-high performance concrete and a preparation method thereof, comprising the following components by mass fraction: natural aggregate 100 parts, magnesium oxide 5 parts, ammonium dihydrogen phosphate 1.5 parts, deionized water 4 parts, and carbon nanotubes 0.5 parts.

[0054] Preparation process:

[0055] 1) Mix 7 parts of magnesium oxide and 2.3 parts of ammonium dihydrogen phosphate to prepare MPC dry powder;

[0056] 2) Add 0.7 parts of carbon nanotubes to the MPC powder, and ball mill at a speed of 1000 r / min for 0.6 hours;

[0057] 3) Mix the composite powder after ball milling with 2.5 parts of deionized water, and continuously stir until the system is uniform to obtain an MPC / CNT composite slurry;

[0058] 4) Load 100 parts of quartz sand aggregate into the hopper of the fluidized bed coating equipment, turn on the equipment, and introduce hot air at 50°C. Adjust the air volume to make the aggregate in a uniform and stable fluidized state. Uniformly apply the prepared MPC / CNT composite slurry in the form of a spray to the surface of the aggregate in a fluidized state through the atomizing nozzle of the equipment. The spraying process lasts for 16 minutes;

[0059] 5) Take out the coated aggregate from the fluidized bed, lay it flat in a tray, ensure good ventilation, and place the tray in a constant temperature and humidity curing box. Curing is carried out at a temperature of 25°C and a relative humidity of 85% for 36 hours to make the MPC coating fully react and completely cure.

[0060] The final coating parameters are: thickness ~ 50 μm, porosity ~ 40%, and average pore size ~ 500 nm.

[0061] Example 5

[0062] This example gives a composite internal curing material for ultra-high performance concrete and a preparation method thereof, which comprises the following components by mass: natural aggregate 100 parts, magnesium oxide 10 parts, ammonium dihydrogen phosphate 3.0 parts, deionized water 2.2 parts, and carbon nanotubes 1.0 part;

[0063] Preparation process:

[0064] 1) Mix 10 parts of magnesium oxide and 3.0 parts of ammonium dihydrogen phosphate to prepare MPC dry powder;

[0065] 2) Add 1.0 parts of carbon nanotubes to the MPC powder, and ball mill at a speed of 1200 r / min for 0.5 hours;

[0066] 3) Mix the composite powder after ball milling with 2.2 parts of deionized water, and continuously stir until the system is uniform to obtain an MPC / CNT composite slurry;

[0067] 4) Load 100 parts of quartz sand aggregate into the hopper of the fluidized bed coating equipment, turn on the equipment, and introduce hot air at 60°C. Adjust the air volume to make the aggregate in a uniform and stable fluidized state. Uniformly apply the prepared MPC / CNT composite slurry in the form of a spray to the surface of the aggregate in a fluidized state through the atomizing nozzle of the equipment. The spraying process lasts for 20 minutes;

[0068] 5) The coated aggregate is taken out from the fluidized bed, laid flat in a tray, and placed in a constant temperature and humidity curing box, with temperature 25℃ and relative humidity 80%, for 48 hours, to make the MPC coating fully react and completely solidify.

[0069] Final coating parameters: thickness ~ 70 μm, porosity ~ 37%, average pore size ~ 300 nm.

[0070] From the above, it can be seen that by reducing the amount of water in the formula, and optimizing the spraying rate and time of the fluidized bed, the thickness of the coating can be accurately controlled.

[0071] Experimental effect verification:

[0072] The composite internal curing material for ultra-high performance concrete of embodiments 1-5 of the present application was subjected to performance testing, and the experimental material was prepared into UHPC with a cement-sand ratio of 1.1 and a water-binder ratio of 0.16. The specific experimental results are shown in Table 1:

[0073]

[0074] The control table clearly shows that by directional design of the coating thickness, porosity and pore size of the composite internal curing material, not only can the final performance of UHPC be significantly improved, but also the early performance development trajectory can be effectively controlled. Whether it is to pursue early strong support, extreme anti-shrinkage or multifunctionalization, it can be achieved by adjusting the coating microstructure, which provides a precise and powerful technical means for the development of high-performance, functional UHPC materials.

[0075] The above is a detailed description of the present application combined with specific embodiments, which cannot be considered as limiting the specific embodiments of the present application to these descriptions. For ordinary skilled persons in the technical field to which the present application belongs, a number of equivalent substitutions or obvious variations can be made without departing from the concept of the present application, and the performance or use is the same, which should be considered as belonging to the patent protection range determined by the submitted claims of the present application.

Claims

1. A composite internal curing material for ultra-high performance concrete and its preparation method, characterized in that, It includes the following raw material components in parts by weight; 100-160 parts natural aggregate; Magnesium oxide 5-12 parts, ammonium dihydrogen phosphate 1.5-3.5 parts, deionized water 1.5-5 parts, carbon nanotubes 0.5-1.2 parts; The magnesium oxide, ammonium dihydrogen phosphate, deionized water, and carbon nanotubes are processed to form an MPC / CNT composite coating, which is then coated onto the surface of the natural aggregate.

2. The composite internal curing material for ultra-high performance concrete and its preparation method according to claim 1, characterized in that: The natural aggregate is quartz sand, and the particle size of the quartz sand ranges from 0.707 mm to 1.19 mm.

3. The composite internal curing material for ultra-high performance concrete and its preparation method according to claim 2, characterized in that: The thickness of the MPC / CNT composite coating is 20 micrometers to 100 micrometers, and the coating has a pore structure with a pore size range of 10 nanometers to 10 micrometers.

4. The composite internal curing material for ultra-high performance concrete and its preparation method according to claim 3, characterized in that: The carbon nanotubes are multi-walled carbon nanotubes with a length of 1-20 μm and a diameter of 5-20 nm.

5. A method for preparing a composite internal curing material for ultra-high performance concrete according to any one of claims 1-4, characterized in that, Includes the following steps: 1) Prepare MPC dry powder by mixing magnesium oxide and ammonium dihydrogen phosphate at a mass ratio of 3-4.5:

1. Add carbon nanotubes at 10% of the mass of magnesium oxide to the prepared MPC powder, and ball mill to obtain carbon nanotube modified MPC composite powder; finally, add deionized water to the modified MPC composite powder, and stir continuously until the system is homogeneous to obtain MPC / CNT composite slurry; 2) Place the natural aggregate in a fluidized bed apparatus to keep it in a fluidized state; apply MPC / CNT composite slurry to the fluidized natural aggregate to complete the coating operation; 3) Curing the coated natural aggregate until the coating is fully cured yields a composite internal curing material for ultra-high performance concrete.

6. The method for preparing a composite internal curing material for ultra-high performance concrete according to claim 5, characterized in that: In step 1), the rotational speed of the ball mill is 600-1200 r / min, and the milling time is 0.5-1 h.

7. The method for preparing a composite internal curing material for ultra-high performance concrete according to claim 5, characterized in that: Step 3) involves a constant temperature and humidity curing method, with curing conditions of 20-25℃, relative humidity of 80%-90%, and curing time of 24-48 hours.

Citation Information

Cited By

  • High-strength multifunctional artificial aggregate and its compression molding preparation method and application

    CN122254859A